Citizen Health Science - Walls, Theodore Adrien; Forkus, Shannon; Coria, Abbigayle (International Journal of Population Data Science, 2019)
Psychology has a long tradition of interest and experience in single subject studies, providing a forerunner scientific platform for person-level trends as they contribute to population data science. Building on this long-standing tradition, population health scientists are increasingly concerned with opportunities to draw inferences about the single case, or studies utilizing an ‘N-of-1’. At the same time, citizen scientists with health interests have become more equipped to conduct their own types of N-of-1 studies given new tools such as smart phone tracking and many other mobile health or “mHealth” devices. These advances in the single case or N-of-1 tradition sometimes involve self-tracking of health data and/or self-experimentation with one’s own health. As networks (increasingly, virtual ones) of people work to maintain or improve their health, a new platform for scientific inquiry has emerged. This paper considers how the confluence of the single case tradition and self-experimentation are key ingredients in a new data science-rich platform, that of citizen health science. Keywords: Citizen health science, single-case designs, single-subject studies, idiographic research, self-experimentation.